PERSEPSI MAHASISWA FKIP UNIVERSITAS RIAU TERHADAP PERNIKAHAN DALAM MASA STUDI - Tumiur Napitu; Elni Yakub; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The progress of the times that have occurred affects various aspects of human life, one of which is in a marriage. In a marriage there will be various problems that require maturity in handling so that a marriage is not seen as mere material readiness, but also mental readiness and maturity to wade through it. Usually the condition where a partner who is unable to resolve and overcome the problems that occur can cause various other problems that can lead to family divorce. This is caused by married decision making that is too concise and lacks consideration for time efficiency so it does not solve the problem but accumulates problems with other problems. Therefore, the authors are interested in conducting research on this matter. The purpose of this study was to determine the extent to which students' perceptions of marriage conducted by students, seeing the phenomena that exist in the faculty and teacher education sciences at the University of Riau, there were several students who had married and continued their studies. This research uses quantitative methods. Data collection techniques in the form of questionnaires. Analyze data using a percentage formula. The sample in this study was 146 students. The results of this study are the perceptions of students who do marriages among students quite well because they can be more mature and independent and quickly get offspring and do not even affect the study being undertaken. The conclusion of this study shows the students' perceptions of marriage among students, namely: 1) cognitive aspects of marriage among students is the knowledge of marriage to prevent premarital sexual behavior; the meaning of marriage to establish a relationship; the benefits of marriage teach how to be responsible; 2) the affective aspects of marriage among students are feelings of fun and motivation in study; easier to adapt; 3) the conative aspect of marriage among students does not affect the studies being undertaken.Key Words: Student Perceptions, Marriage Among Students